Perluasan Alat Bukti Petunjuk dalam Tindak Pidana Pencucian Uang dari Tindak Pidana Asal Korupsi - Nurdiana, Gilang; Budiman, Maman (Universitas Batanghari Jambi, 2025)
This article will examine circumstantial evidence in money laundering crimes and the expansion of circumstantial evidence in money laundering crimes from the original crime of corruption. The research method applies descriptive analytical research specifications and uses a normative legal research approach. The research data collection technique was obtained from literature and document studies. The data obtained was then analyzed qualitatively from a legal perspective, emphasizing legal analysis with formal thinking concepts and presented in the form of arguments. The results of the study show that circumstantial evidence in money laundering crimes can be obtained from evidence as referred to in Article 188 (2), namely witness testimony, letters, defendant testimony, and electronic evidence as referred to in Article 73 letter b of Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. The expansion of circumstantial evidence needs to be pursued by expanding the evidence that serves as preliminary evidence of suspicious financial transactions with electronic evidence in the form of derived evidence, which will be useful in determining legal steps in the form of investigations or in proving cases in court, and needs to be reinforced with statements from financial transaction analysis experts.